Self-, peer-, and teacher-assessment: An investigation into Iranian EFL students’ attitudes - Khonbi, Zainab Abolfazli; Sadeghi, Karim (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2013)
Student-directed teaching and assessment techniques are gradually dominating educational systems almost all over the world. This study investigated a cohort of male and female Iranian EFL students’ attitudes toward self-, peer-, and teacher-assessment experiences. Sixty three students at Urmia University and Tabriz Islamic Azad University, in the form of three intact classes, experienced self-, peer-, and teacher-assessment activities for one academic semester (having taken a knowledge pretest, four assessment series, and a course achievement posttest). Of all the participants, 38 completed a 5-point Likert-scale attitude questionnaire. The application of ANOVA, across and within group dependent samples t tests, as well as some qualitative analyses, indicated that the three experimental groups had positive attitudes toward their assessment experiences. While the peer-assessment group was the most positive in this regard, slight differences were found in the groups’ attitudes and beliefs. Further findings and implications are discussed in the paper.
Keywords: teacher assessment; course achievement; peer-assessment; self-assessment; student attitudes